Management Science in Managing the Supply Chain of Food Security System - Rahman, Arief (2015)
Many academics utilise management science or operational research (MS/OR) for business purposes. Specifically, MS/OR methods have played important roles in managing the profitability and the robustness of the food supply chain in the private sector; for example, by maximising income, improving efficiency and managing risk. However, there have been few published studies investigating the application of MS/OR methods from a public sector perspective. Discussions regarding food sector management in the context of the public sector are relevant for food security system management. This dissertation investigates the importance of applying MS/OR methods to policy making in the public food supply chain, and further links them with food security (availability, access to food, utility and stability) sustainment. Therefore, MS/OR methods become evidenced-based to further support policy making in the public food supply chain, from planning to monitoring and evaluation.